The Use of the Symbol of the Moon in Uzbek Literature - Berdiyeva Nilufar (Researchparks Publishing, 2022)
This article analyzes the processes associated with the application of the Moon symbol in the literature. The representation of beautiful and delicate women in the symbol of the moon has been shown to be an important feature of Eastern literature. The convenience of creators through the symbolic depiction of celestial bodies in literature has been studied on the example of specific works. In poetic works, the use of the symbol of the moon in the sense of a beloved companion has long been proved. The analysis of some short stories shows that prose works are still used today to describe women of different natures through the image of the moon. In this regard, attention is drawn to the fact that the image of the sun also occurs in the adjacent position. In general, it summarizes how the use of symbols in works of art affects works.